Genome-wide identification and characterization of HSP gene superfamily in whitefly (Bemisia tabaci) and expression profiling analysis under temperature stress - Wang, Xin-Ru; Wang, Chao; Ban, Fei-Xue; Zhu, Dan-Tong; Liu, Shu-Sheng; Wang, Xiao-Wei (My University, 2019)
Heat shock proteins (HSP) are essential molecular chaperones that play important roles in the stress stimulation of insects. Bemisia tabaci, a phloem feeder and invasive species, can cause extensive crop damage through direct feeding and transmission of plant viruses. Here we employed comprehensive genomics approaches to identity HSP superfamily members in the Middle East Asia Minor 1 whitefly genome. In total, we identified 26 Hsp genes, including three Hsp90, 17 Hsp70, one Hsp60 and five sHSP (small heat shock protein) genes. The HSP gene superfamily of whitefly is expanded compared with the other five insects surveyed here. The gene structures among the same families are relatively conserved. Meanwhile, the motif compositions and secondary structures of BtHsp proteins were predicted. In addition, quantitative polymerase chain reaction analysis showed that the expression patterns of BtHsp gene superfamily were diverse across different tissues of whiteflies. Most Hsp genes were induced or repressed by thermal stress (40°C) and cold treatment (4°C) in whitefly. Silencing the expression of BtHsp70-6 significantly decreased the survival rate of whitefly under 45°C. All the results showed the Hsps conferred thermo-tolerance or cold-tolerance to whiteflies that protect them from being affected by detrimental temperature conditions. Our observations highlighted the molecular evolutionary properties and the response mechanism to temperature assaults of Hsp genes in whitefly.
Keywords: cold stress; comparative genomics; HSP; phylogenetic; thermal stress; whitefly